Religious tolerance in Islam : theories, practices and Malaysia’s experiences as a multi racial society - Fadzil, Ammar (International Islamic University Malaysia, 2011)
Religious tolerance in Islam can be looked at from two perspectives: firstly, the theory of religious tolerance particularly propounded in the Qur’an; secondly, the practices of religious tolerance exemplified by the Prophet Muhammad and his Successors. Islam as a religion consists of certain principles that deal with its adherents and non-adherents. Some of these principles are very fundamental for Muslims, who raise a question as to what extent Islam allows its adherents to tolerate others in matters that affect these fundamental principles. This question is very much relevant to multi-racial and multi-religious Malaysia which has its experiences of harmony among its various religious communities, reducing tension within the society. This article discusses all these dimensions of religious tolerance with special reference to Malaysia, concluding that tolerance can be achieved only when there is a mutual understanding amongst the members of a society and an eagerness to respect each other’s rights.